Associations between Global Diet Quality Score (GDQS) and obesity in women of reproductive age in Northern Tanzania: A cross-sectional study - Bliznashka, Lilia; Azupogo, Fusta; Reynolds, Elise; Arnold, Charles D.; Hess, Sonja Y.; Kinabo, Joyce; Jeremiah, Kidola; Malindisa, Evangelista; Olney, Deanna K.; Ruel, Marie T. (Elsevier, 2026)
Background Obesity is an increasing problem among women of reproductive age (WRA) in Tanzania.